The Philippine economic take-off: A myth, an elusive reality or an anachronistic perspective? - Tullao, Tereso S., Jr. (Animo Repository, 2013)
The economic takeoff was first introduced by Walter Rostow in the 1960’s as part of the five stages of growth that an economy has to pass towards full development. These stages present an alternative perspective in analyzing the economic performance of a country in contrast from the Marxian view. The stages consist of the traditional society, pre-conditions for takeoff, takeoff, drive to maturity, and age of mass consumption. In addition, they are accompanied by distinct changes in politics, technology, society and the economy. Economic transformations are shown by rapid capital accumulation, development of one or more industries particularly in manufacturing, and the emergence of political, social and institutional structures that bring about changes towards the expansion of the modern sector, the use of capital in business and mobilization of resources. In the light of these conditions, has the economy of the Philippines taken-off towards sustained growth? If it has not, what are the reasons preventing it in attaining these requirements for takeoff? If, however, these conditions have been fulfilled why is the Philippine economy still not considered a developed economy? Is economic takeoff an elusive goal or a myth? Or is it an anachronistic view of economic development?